HUBUNGAN KEADAAN LINGKUNGAN DENGAN KEJADIAN INFEKSI SALURAN PERNAFASAN AKUT (PNEUMONIA) PADA BALITA - Rajagukguk2, Marlina; Simanungkalit, Abram; Situmorang, Nasib M (Viva Medika, 2021)
Abstract Pneumonia is a major cause of morbidity and mortality in children under five years of age, especially in developing countries. Pneumonia is "the leading killer of children worldwide" and is often neglected so that pneumonia is called the forgotten killer of children. Among the five deaths in children under five, one of them was caused by pneumonia. Pneumonia risk factors can come from environmental factors such as exposure to cigarette smoke and the host in the form of poor nutritional status. Knowing the relationship between exposure to cigarette smoke and the incidence of pneumonia in toddlers and knowing the relationship between nutritional status and the incidence of pneumonia in. This research is a research using the method of literature review. Data obtained from secondary data using documentation techniques. Data documentation is based on journals related to research variables. There is a relationship between nutritional status in children under five with the incidence of pneumonia in children under five. There is a relationship between exposure to cigarette smoke and the incidence of pneumonia in children under five.